Development of flexible radiation shielding materials from natural Rubber/Sb2O3 composites. (November 2022) - Yonphan, S.; Chaiphaksa, W.; Kalkornsurapranee, E.; Tuljittraporn, A.; Kothan, S.; Kaewjaeng, S.; Intachai, N.; Wongdamnern, N.; Kedkaew, C.; Kim, H.J.; Kaewkhao, J.
Abstract: In this paper, a natural rubber (NR) with the addition of antimony oxide (Sb2 O3 ) has been developed for flexible radiation shielding materials. The composites of NR were prepared various amounts of Sb2 O3 concentrations. The mechanical properties including modulus at 100% elongation, tensile strength, elongation at break, hardness, and specific gravity of the NR composites were investigated. The gamma-ray shielding properties were measured in the energy range of 0.223 MeV–0.662 MeV by using the Compton scattering technique and compared with the theoretical values. From the results, it was found that the values of mass attenuation coefficient ( μ m ), effective atomic number ( Z e f f ), and effective electron density ( N e f f ) increased with an increase of the Sb2 O3 content. For the X-ray shielding properties, the mass attenuation coefficient ( μ m ) of NR composites was also higher with increasing Sb2 O3 concentration. Moreover, the half-value layer (HVL) of 20, 40, and 100 phr composites have been improved compared to the commercial windows, concrete, and red brick. These results reflected that the NR/Sb2 O3 composites are suitable for use as flexible radiation shielding materials. Highlights: New flexible shielding materials made from natural rubber (NR). Natural rubber/Sb2 O3 enhanced shielding properties for gamma and X-ray. Shielding properties show better than commercial windows, concrete, and red brick. Natural rubber/Sb2 O3 composite is suitable for use as flexible radiation shielding materials.